2021
DOI: 10.1016/j.fuel.2020.119517
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the influence of hydrogen as a fuel additive on the formation of soot precursors and particles in atmospheric laminar premixed flames of methane

Abstract: We report here the experimental investigation of lightly sooting methane premixed flames with and without hydrogen. Two different approaches were considered to introduce hydrogen in the methane flame, either by keeping the total gas flow rate constant or not. Speciation data were obtained using a set of analytical tools including Gas Chromatography, Fourier-Transform Infrared Spectroscopy, Jet-Cooled Laser-Induced Fluorescence, Laser-induced Incandescence coupled with Cavity Ring-Down Spectroscopy.The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 81 publications
(126 reference statements)
9
23
0
Order By: Relevance
“…Moreover, not all of the considered mechanisms include PAH larger than pyrene. Pyrene has been shown in numerous previous studies that it was a species close enough to actual precursors to give good tendencies [1,26,28,29,75,[94][95][96][97][98]. Thanks to the experimental data provided in the previous sections, the influence of this simplifying assumption is evaluated in Section 3.3 with the introduction of cases using all PAH larger than pyrene for particle inception and PAH adsorption/desorption in the cases using the KAUST mechanism.…”
Section: Soot Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, not all of the considered mechanisms include PAH larger than pyrene. Pyrene has been shown in numerous previous studies that it was a species close enough to actual precursors to give good tendencies [1,26,28,29,75,[94][95][96][97][98]. Thanks to the experimental data provided in the previous sections, the influence of this simplifying assumption is evaluated in Section 3.3 with the introduction of cases using all PAH larger than pyrene for particle inception and PAH adsorption/desorption in the cases using the KAUST mechanism.…”
Section: Soot Modellingmentioning
confidence: 99%
“…Recently the existence of nucleation flames, burning different fuels and at different pressures, in which soot particles undergo negligible growth with residence time in the flame, has been demonstrated [24][25][26][27][28]. In these flames, the soot particles remain at constant diameter around 2-4 nm along the height above the burner (HAB) [27] and the soot volume fraction increases mainly by its number of smallest measurable soot particles, which are issued from the overall nucleation process [26].…”
Section: Introductionmentioning
confidence: 99%
“…A purely chemical growth of aromatics, i.e., the extension of the PAH size by addition of gaseous species, such as acetylene, is insufficient to explain the size of emerging soot particles; the particle size is determined by particle coagulation . The latter assertion was suggested by early transmission electron microscopy of soot particles and phenomenological analysis of their time evolution, which was later corroborated by detailed modeling. , A more recent affirmation comes from high-quality experimental observations of particle nanostructure, showing that particle constituents are largely middle-range (four-to-seven-ring) PAHs. …”
mentioning
confidence: 99%
“…We recently also showed that the introduction of H2 in a nucleation methane flame (C=1.82), i.e. a flame generating only nascent soot particles [32], drastically reduced or enhanced the formation of aromatic species and the soot volume fraction, depending on the way of introducing H2 (either by addition or substitution to the diluent). However, these flames did not allow studying the soot growth process and the impact of H2 on the soot particles distribution and soot number density.…”
Section: Introductionmentioning
confidence: 99%